유기물 첨가제가 마이크로 패턴 구리 전주 도금에 미치는 영향 연구 - 이주열(Joo-Yul Lee); 김만(Man Kim); 이규환(Kyu Hwan Lee); 임성봉(Seong-Bong Yim); 이종일(Jong Il Lee) (Biuletyn Uniejowski, 2010)
The effect of organic additives, 1-(3-sulfoproyl)-2-vinylpyridineium hydroxide (SVH) and thiourea (TU), on the precision copper electrodeposition was investigated with optical, electrochemical and x-ray diffraction techniques. It was found that SVH played a r ole as a n accelerator and TU as an i nhibitor during the electroreduction of cupric ions in acidic Cu electroplating solution. Through electrochemical measurements, TU showed more strong interaction with cupric ions than SVH and dominated overall Cu electroplating process when both additives were present in the solution. In the case of three dimensional Cu electrodeposition on the 20 ${μ}m$-patterned Ni substrates, SVH controlled the upright growth of Cu electrodeposits and so determined its flatness, while TU prohibited the lateral spreading of Cu in the course of pulse-reverse pulse current adaptation. With microscopic observation, we obtained the optimum organic additives composition, that is, 100 ppm SVH and 200 ppm TU during the current pulsation.